L’opérationnalisation Des Politiques Publiques Face A La Négociation Et La Marchandisation Politiques Au Bénin De 2006 A 2016 - Gbenou, Victorin Vidjannagni (European Scientific Journal, ESJ, 2018)
This paper focuses on the politicization of the operationalization of public policies in Benin from 2006 to 2016. Here, the phenomenon has been accentuated with the direct consequence of questioning the relevance of public action. Its overall objective is to analyze the political practices that have supported the operationalization of public policies from 2006 to 2016. In answering the research question asked, the variables generated by the working hypotheses are related to political negotiation, political haggling, and political blackmail. The research is anchored on the theoretical current interactionist. It is both qualitative and quantitative at the same time. The data were collected from stakeholders involved in the process in Cotonou, Porto-Novo, and Parakou from September 2017 to June 2018. The sample consists of 247 actors (16 for interviews, 231 informants per questionnaires). Informants were selected using reasoned choice and random choice after Schwartz’s formula. The analysis of the result shows that political negotiation requires promises around public policies to be more conclusive while relying on the various lobbies. Political commodification leads to an open market on which public markets, business, posts and political investments, and public policies are found. Political blackmail is being implemented at the time based on the operationalization of public policies. Political support is a guarantee and the outcome of public policies is significantly dependent on the vote.